2012
DOI: 10.4085/1062-6050-47.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ankle Instability and Corticomotor Excitability of the Fibularis Longus Muscle

Abstract: Context: Neuromuscular deficits are common in people with chronic ankle instability (CAI). Corticomotor pathways are very influential in the production of voluntary muscle function, yet these pathways have not been evaluated in people with CAI.Objective: To determine if corticomotor excitability of the fibularis longus (FL) differs between individuals with unilateral CAI and matched control participants without CAI.Design: Case-control study. Setting: Laboratory.Patients or Other Participants: Ten people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 39 publications
2
82
1
Order By: Relevance
“…6 Other investigators have reported reduced corticomotor excitability of the fibularis muscles among individuals with unilateral chronic ankle instability compared to healthy individuals. 7 Should dry needling of the fibularis muscles have any effect on their cortiomotor excitability or reaction time, this may explain an increase in performance on unilateral balance tests and are future areas of investigation. If dry needling the multifidi has any inhibitory effect on the fibularis muscles, then the effects of needling spinally may negate the facilitory effects of dry needling the fibularis muscles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Other investigators have reported reduced corticomotor excitability of the fibularis muscles among individuals with unilateral chronic ankle instability compared to healthy individuals. 7 Should dry needling of the fibularis muscles have any effect on their cortiomotor excitability or reaction time, this may explain an increase in performance on unilateral balance tests and are future areas of investigation. If dry needling the multifidi has any inhibitory effect on the fibularis muscles, then the effects of needling spinally may negate the facilitory effects of dry needling the fibularis muscles.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigators have shown abnormalities of the fibularis muscles in persons with CAI, including reduced reaction time, diminished postural control and corticomotor excitability, and the presence of myofascial trigger points (MTrPs). 5,6,7 MTrPs are areas of increased irritability in palpable taut bands of skeletal muscle tissue that are clinically associated with both local and referred pain, muscle dysfunction, and autonomic phenomena. [8][9][10] In addition to other intervention strategies, the use of dry needling as a treatment for MTrPs is gaining attention as investigations on its effectiveness emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Resting motor thresholds of the fibularis longus were bilaterally higher in patients with unilateral CAI than in control participants, 23 suggesting that unilateral injury may cause bilateral alterations of corticospinal excitability or that these alterations were present before injury and potentially led to the development of CAI. Bilateral deficits in quadriceps neuromuscular control have been reported after unilateral anterior cruciate ligament injury, 42 suggesting that bilateral neuromuscular alterations are common after unilateral injury at joints in addition to the ankle.…”
Section: Discussionmentioning
confidence: 92%
“…22 Similarly, corticospinal excitability of the fibularis longus in CAI patients has been shown to be diminished when compared with healthy participants assessed using transcranial magnetic stimulation (TMS). 23 Neuromuscular control adaptations in joints proximal to the ankle also have been demonstrated in patients with CAI, manifesting as deficits in force production, 17,24 changes in kinematic patterns, 10,11,14,[25][26][27] and deficits in muscle-activation patterns 12,[28][29][30][31] about the knee and hip during slow and dynamic tasks. Whereas these alterations are observed consistently, the source of these changes has not been established.…”
mentioning
confidence: 99%
“…Physical disability subsequent to recurrent ankle sprains has included range of motion and strength deficits, sensorimotor alterations, balance impairments, gait alterations and post-traumatic osteoarthritis [9][10][11][12][13][14][15]. Current research in these areas has focused on improving function and lessening disability associated with this condition, as well as identifying what leads to recurrent sprains.…”
Section: Introductionmentioning
confidence: 99%